Fatal outbreak among camels in Kazakhstan associated with Paeniclostridium sordellii - Karamendin, K.; Kydyrmanov, A.; Seidalina, A.; Kirkimbayeva, Zh.; Ozgan, S.; Fereidouni, S. (Fundamental and Experimental Biology, 2022)
An outbreak of a bacterial disease with lethal cases was registered in camels in Kazakhstan in 2018. The dis-ease was characterised by dry, harsh hacking cough and nasal discharge with froathy and bloody liquid. Cam-els died in a state of hyperexcitement and asphyxia. Investigation of the case has identified the pathogenic form of Paeniclostridium sordellii as the main cause of mortality in camels. The purpose of the study is to identify the cause of mortality among camels, bacteriological and molecular genetic characteristics of the pathogen. The methodological basis of the work is collection of biological samples from camels, isolating the pathogen on media, extracting nucleic acids, obtaining libraries for next generation sequencing, bioinformatic analysis of the obtained data, pathogenicity test on mice. This article describes the cultural, genetic and phenotypic characteristics of the isolated Shetpe PS18-01 strain. It was shown that the pathogenesis was mainly characterised by respiratory signs, in contrast to the most common gastrointestinal ones.